Alterations in running economy and mechanics after maximal cycling in triathletes: influence of performance level - Millet, G. P.; Millet, G. Y.; Hofmann, M. D.; Candau, R. B. (International Journal of Sports Medicine, 2000)
The effects of the triathlon performance level on the metabolic and mechanical alterations in running after an exhaustive cycling exercise were studied. Eight elite and 18 middle-level triathletes completed two 7 min runs on a treadmill at a velocity corresponding to that sustained during a triathlon before and after maximal cycling exercise. Energy cost of running was quantified during the last minute of each run from the net oxygen uptake. External mechanical cost was quantified during the last minute of each run from displacements of the centre of mass using a kinematic arm. The effect of cycling on the running energy cost differed when comparing the elite (from 4.01+/-0.46 to 3.86+/-0.34J x kg(-1) x m(-1)) and the middle-level triathletes (from 3.67+/-0.37 to 3.76+/-0.39 x kg(-1) x m(-1) (P<0.01). The effect of cycling on the respiratory muscle O2 was more important (P<0.05) for the middle-level (from 120.1+/-27.2 to 166.4+/-47.8 ml x min(-1)) than for elite triathletes (from 124.5 +/- 24.5 to 143.7 +/- 28.9 ml x min(-1)). A tendency to a decrease of the mechanical cost and of the vertical displacement of the centre of mass during the braking phase was observed for the elite triathletes, suggesting a better leg stiffness regulation than for their less successful counterparts.